Effects of oral glucose tolerance test on microvascular and autonomic nervous system regulation in young healthy individuals - Kralj, Lana; Battelino, Tadej; Lenasi, Helena (Scientific reports, 2025)
Acute elevations in blood glucose can influence microvascular function and autonomic nervous system (ANS) reactivity, both implicated in cardiometabolic risk. We assessed the effects of oral glucose tolerance test (OGTT) on microvascular and ANS physiological responses in healthy young individuals. Using laser Doppler flowmetry (LDF), we measured basal skin microcirculatory blood flow and responses to post-occlusive reactive hyperemia, iontophoresis of acetylcholine (ACh), and sodium nitroprusside (SNP) in 28 participants before and 45 and 120 min after OGTT or water loading. LDF spectral components were analyzed using wavelet analysis (WA). ANS reactivity was evaluated from electrocardiogram recordings by analyzing heart rate variability (HRV). OGTT caused time-dependent changes in microvascular and HRV parameters. Endothelial nitric oxide-independent vasodilation transiently decreased during SNP response ( p = 0.014), while myogenic component transiently increased ( p = 0.029; two-way repeated measures ANOVA), with no significant change in the endothelial nitric oxide-dependent component. HRV measures RMSSD ( p = 0.009) and SDNN ( p = 0.008) decreased. Oral glucose loading affects microcirculation in healthy individuals, likely through modulation of endothelial nitric oxide-independent signaling, vascular smooth muscle responsiveness, and ANS reactivity. WA may offer a sensitive method for detecting microvascular dysfunction associated with physiological changes following oral glucose loading.